Variable valve timing on piston engine for lightweight aircraft. - Sabaruddin, Ainul Aniyah; Wiriadidjaja, Surjatin; Abang Abdul Majid, Dayang Laila; Djojodihardjo, Harijono; Ahmad, Mohamed Tarmizi (2012)
As Lycoming engine failed attempt on using the variable valve timing for aircraft piston engine back in 1940’s, the idea of the technology is abandoned as turbine are then introduced in the aviation field with practical use and greater power. Since piston engines produced smaller power than turbines, it is still practically used for lightweight aircraft presently. Back then, the project failed due to size problem as the size of piston was much bigger and heavier. Nowadays conventional piston engines, with smaller and lighter size and weight of the engine, give possibility to reinvent the idea of using variable valve timing system (VVT) on piston engines for lightweight aircraft. With the use of this new valve system, increases in power output and lesser fuel efficiency of automobile engines have been indicated. The indicated improvements, however, are constraint to automobile engines running with high RPMs only. Engine simulation program was run in this investigation to predict the engine performances appropriate for lightweight aircrafts with a few assumptions for ideal condition.